Endogenous and Exogenous Regulatory Signaling in the Secretory Pathway: Role of Golgi Signaling Molecules in Cancer - Del Giudice, Simona; De Luca, Valentina; Parizadeh, Seyedehnegar; Russo, Domenico; Luini, Alberto; Di Martino, Rosaria (Frontiers in Cell and Developmental Biology, 2022)
The biosynthetic transport route that constitutes the secretory pathway plays a fundamental role in the cell, providing to the synthesis and transport of around one third of human proteins and most lipids. Signaling molecules within autoregulatory circuits on the intracellular membranes of the secretory pathway regulate these processes, especially at the level of the Golgi complex. Indeed, cancer cells can hijack several of these signaling molecules, and therefore also the underlying regulated processes, to bolster their growth or gain more aggressive phenotypes. Here, we review the most important autoregulatory circuits acting on the Golgi, emphasizing the role of specific signaling molecules in cancer. In fact, we propose to draw awareness to highlight the Golgi-localized regulatory systems as potential targets in cancer therapy.